Morfologia plagiatu - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Authorship, as a protected good, is never entirely secure. Plagiarism is a practice that has been perpetually present in human culture. This monographic essay dedicated to plagiarism offers a broad, panoramic view of its occurrence in science, art, and other creative fields. The author posits that the true subject of plagiarism is not the substance of the plagiarized text (words, sounds, images), but its essence, namely the original authorial thought – the original concept, idea, or creative vision contained within the structure of the original work.